Synthesis and Theoretical Studies of Methyl 2-[(2-oxo-2H-chromen-4-yl)oxy]acetate - A. Al-Amiery1, Ahmed; R. Obayes1, Hasan; H. Alwan3, Ghadah; Amir H. Kadhum2, Abdul; Bakar Mohamad2, Abu (Asian Journal of Chemistry, 2013)
A derivative of 4-hydroxycoumarin, namely, methyl 2-[(2-oxo-2H-chromen-4-yl)oxy]acetate was synthesized and characterized by means of it UV-visible, FT-IR, 1H-NMR and 13C-NMR spectral data. Research has included finding the best method of calculation to six kinds of stretching vibration frequencies contained within the molecule {methyl 2-[(2-oxo-2H-chromen-4-yl)oxy]acetate}. Chosen four DFT models are given by combining the exchange and correlation functional and four basis set to get sixteen different method of calculating. It is found that the best method of calculation to frequency of stretching vibration for (C-H) bond is (HCTH/DGTZVP), for frequency of stretching vibration for (C=O, ester) bond is (MPW1PW91/ LanL2DZ), for frequency of stretching vibration for (C=O, lactone) bond is (HCTH/LanL2DZ), for frequency of stretching vibration for (C=C) bond is (B3LYP/DGTZVP). While calculations showed that the method (HCTH/DGTZVP) needs time more than the rest of the calculation methods.